Fractionation and characterization of extracted lignin from oil palm empty fruit bunch using synthesized deep eutectic solvents / Tan Yee Tong - Tan , Yee Tong (2020)
Deep eutectic solvent (DES), a new generation green solvent has been introduced as an alternative pretreatment solvent due to its ability for lignocellulosic biomass fractionation and lignin extraction. Numerous types of compounds can be adopted as DES constituents, which has resulted in abundant variation of DES with varying properties. Selection of the suitable chemical compound category is therefore essential for optimum DES performance. However, investigation on the performance comparison between the different DES categories is lacking. In addition, despite its widely acknowledged effectiveness in biomass fractionation, the properties of DES-fractionated biopolymers, especially lignin are not well understood. Hence, this project focused on identifying the best performing DES constituents for lignocellulosic biopolymer fractionation and lignin extraction from oil palm empty fruit bunch (EFB). Subsequently, the properties of DES-pretreated EFB solid and DES-extracted lignin (DEEL) were elucidated to assess their potential for downstream conversion. EFB was selected as the source of biomass in this study due to its presence as one of the most abundant agricultural wastes in Malaysia and its rich lignocellulosic biopolymer content. The first stage of DES selection started with identifying the suitable pH range of the solvent. Acidic DES demonstrated great fractionation ability to achieve 100% of glucan retention in DES-pretreated biomass solid, 100% of hemicellulose hydrolysis, and 50.6% of lignin extraction. The fractionation performance of alkaline and neutral DESs were comparatively inefficient. To optimize the DES performance, types of acid constituent hydrogen bond donor (HBD) in DES that promoted EFB fractionation and lignin extraction were next investigated based on the acid’s functional group and molar ratio. The results showed that the presence of hydroxyl group (-OH) and short alkyl chain (-CnH2n+1) in the acid HBD could enhance lignin extraction and biomass fractionation performance. As a result, choline chloride:lactic acid (CC-LA) 1:15 and choline chloride:formic acid (CC-FA) 1:2 achieved the highest lignin extraction yield at >60 wt% when compared with the other acidic DESs. The EFB solid fractionated by both acidic DES were enriched with >80 wt% of glucan content. The type of DES solvent applied in lignin extraction process significantly affect the isolated lignin’s composition, molecular structure, thermal properties and their compatible downstream conversion technologies. CC-LA DEEL would be more suitable for functional modification as shown through the higher amount of labile β-O-4 linkage (2.52 unit/Ar) and volatile product emission. CC-FA DEEL encompassed a highly condensed structure due to the abundant C-C linkages formed via the extensive hydrolysis of ether bond. A circular biorefinery process was then proposed, in which the process was initiated with DES pretreatment for biopolymer fractionation and followed by the conversion of DES-fractionated biopolymers into bio-based materials or chemicals. This study demonstrates a step-wise DES constituent selection process for lignocellulosic biomass pretreatment. The findings obtained is expected to aid in the selection of DES solvent for efficient biomass fractionation, thus providing an alternative solution to the lagging development of the lignocellulosic biomass conversion, such as oil palm empty fruit bunch into a variety of bio-based products.